2021
DOI: 10.21037/tlcr-20-1067
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic biomarkers in oligometastatic non-small cell lung cancer: a literature review

Abstract: This review aims to summarize the possibilities of recently discovered molecular diagnostic techniques in lung cancer, by evaluating their impact on diagnosis, monitoring, and prognosis in oligometastatic disease.Background: Oligometastatic non-small cell lung cancer (OM-NSCLC) is currently defined based on morphological rather than biological features. Major advances in the detection of molecular biomarkers in cell-free tumoral DNA and the models of oncogene addiction make as feasible an early diagnosis and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…In addition to the number of metastases, the size and location of metastases have an impact on the prognosis. The identification of related biological markers, such as cell-free DNA and circulating tumor cells, is urgently needed to identify the disease characteristics of oligometastasis that may benefit from LAT 45 , 47 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the number of metastases, the size and location of metastases have an impact on the prognosis. The identification of related biological markers, such as cell-free DNA and circulating tumor cells, is urgently needed to identify the disease characteristics of oligometastasis that may benefit from LAT 45 , 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The meta-analysis included six oligometastases and one polymetastasis NSCLC studies; therefore, some heterogeneity was considered. A systematic review should collect all available evidence, and the purpose of a meta-analysis is to provide integrated information based on extensive literature to help clinical decisions, as referenced in the Cochrane manual 46 , 47 . The previous study included only six oligometastasis studies, which required a more extensive search, and no subgroup analyses were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Even more interesting would be the ability to distinguish a oligometastatic state through liquid biopsies: detecting relevant biological molecules and macrostructures in peripheral blood, such as circulating tumor DNA (ctDNA), circulating microRNA, circulating free RNA, extracellular vesicles, or circulating tumor cells [60]. Recent studies have indicated the clinical utility of ctDNA for molecular residual disease assessment, monitoring recurrence, and treatment response in patients, with emerging applications in oligometastatic patients [61][62][63][64][65].…”
Section: Biomarkers In Oligometastatic Diseasementioning
confidence: 99%
“…Although interpretation is limited by small sample size, these findings may suggest that the survival benefit associated with LAT may be mediated by enhanced early immune-mediated tumor killing in oligometastatic NSCLC and that ctDNA could be used post-LAT for the assessment of tumor response and/or early recurrence. However, care should be taken with this approach as levels of ctDNA shedding can vary among patients with intrathoracic only versus extra-thoracic involvement of disease [ 74 ].…”
Section: Future Directionsmentioning
confidence: 99%